Kreativitas Siswa pada Proses Pembelajaran Tari Kreasi (Zapin Melayu) di SMP Negeri 4 Siak Hulu - Adinda Leni; Nurmalinda Erawati (Advances In Education Journal, 2025)
This study aims to describe the creativity of seventh-grade students in the cultural arts learning of Zapin Melayu creative dance at UPT SMP Negeri 4 Siak Hulu. Student creativity was analyzed through five indicators: fluency, flexibility, originality, elaboration, and sensitivity. The research employed a qualitative descriptive method with data collected through observation, interviews, and documentation. The results showed that students demonstrated a good level of creativity in generating varied dance movements, collaboratively developing movement ideas, and expressing themes appropriately. Assessment of wiraga (movement technique), wirama (rhythm), and wirasa (expression) showed that most students were in the "good" to "very good" category. The teacher facilitated learning through an interactive approach and provided space for exploration, allowing students to optimize their creative potential. This study highlights the importance of contextual and creative learning strategies to foster artistic expression and student innovation in school-based dance education.